Teens and tobacco : a fatal attraction - Lang, Susan S.; Marks, Beth H. (New York : Twenty-First Century Books, 1996)
Discusses the effect of smoking on teenagers and why they smoke.
Includes index.
Keywords: Teenagers -- Tobacco use -- Juvenile literature; Tobacco use -- Juvenile literature; Smoking; Tobacco use